Community Assistance in Preventing Hypertension Emergencies Through Improving Germas Behavior in The Working Area of Pucang Sewu Health Center Surabaya City - Proboningsih, Jujuk; Widyastuti, Dwi; Anita Joeliantina; Alberta, Lembunai Tat Alberta (Frontiers in Community Service and Empowerment, 2024)
Hypertension is one of the most common and most common heart and blood vessel diseases in the community. Death from hypertension is generally caused because in the early stages people do not understand the early symptoms of emergencies that have an impact on death from hypertension. . Deaths from hypertension can be minimized, among others, by increasing public understanding in preventing hypertensive emergencies through improving Germas behavior by: increased physical activity, consumption of vegetables and fruits, regular health checks and not smoking. In addition, community skills are also needed in measuring and monitoring blood pressure independently in order to be able to carry out early detection of the occurrence of hypertensive emergencies. This community service activity is carried out using lectures, questions and answers and training methods to measure blood pressure independently. The results of the activity were in the form of providing education on the prevention of hypertension emergencies and training on independent blood pressure measurement to 60 people with hypertension in the working area of the Pucang Sewu health center in Surabaya City. Conclusion People understand about the prevention of hypertension emergencies and are skilled in measuring blood pressure independently.